Persepsi Wisatawan Terhadap Komponen Produk Pariwisata 4A pada Daya Tarik Wisata Trans Studio Bali, Desa Pemecutan Kelod, Kecamatan Denpasar Barat, Kota Denpasar, Bali - Angeline, Angeline; Anom, I Putu (JURNAL DESTINASI PARIWISATA; Vol 11 No 2 (2023): VOL 11, NO 2 (2023): (JULY-DECEMBER) JURNAL DESTINASI PARIWISATADO - 10.24843/JDEPAR.2023.v11.i02.p15, 2023)
Trans Studio Bali is a man-made tourist attraction that takes the concept of a thematic amusement park, offers exciting international-class rides, and has management of its 4A tourism product components in order to realize sustainable tourism. By knowing the perceptions of tourists arising from tourism management, this can support improving the quality of tourism in this tourist attraction. This research uses a type of quantitative descriptive research and data collection is done through participatory observation, questionnaires, documentation, and literature study. Sampling used purposive sampling with a closed-ended questionnaire using a Likert Scale. The theory used in this research is Perception Theory. The results of the study show that people's perceptions tend to be positive towards the presence of tourism product components in the tourist attraction of Trans Studio Bali. Therefore, it is hoped that the suggestions and expectations from tourists can be used as a reference to continue to improve the quality of the 4A tourism product components at the Trans Studio Bali tourist attraction. Keywords: Tourist Perception, Tourism Product Component